Influence of emotional intelligence on the development of entrepreneurial skills in an entrepreneurship course - Quispe Rivera, Teotista Adelina (2025)
This research addresses the question: How does emotional intelligence (EI) influence the entrepreneurial skills (ES) of students in an entrepreneurship course? The course is designed for students in the final semester of technological degree programs at a higher education institution. The course aims to foster both technical knowledge and soft skills, thereby cultivating young entrepreneurs through a comprehensive assessment of both components. This study adopted a quantitative, non-experimental design and included a sample of 116 students aged between 19 and 25. The validated linear regression model yielded an r value of 0.351 and an r2 value of 12.3%. The findings indicate that EI significantly influences ES. Furthermore, intrapersonal intelligence was found to have a greater impact on the development of ES than interpersonal intelligence. The study also identified the need to strengthen two key entrepreneurial skills: information seeking and commitment to activities undertaken. Accordingly, implementation strategies are proposed to address this need.